Entity-relation modeling and discovery for smart search - Sean WANGX; Xiao-qing ZHENG; Yang-hua XIAO (Tongxin xuebao)
Nowadays,by connecting the mobile networks,Internet of Things and the sensor networks to the Internet,the cyberspace has expanded to a ubiquitous space of human beings,machines and things.Combining with the technology of big data,the traditional search engines are evolving into their next generation—big search (or smart search).Entity-relation modeling and discovery are the key techniques to fulfill the vision of smart search.Approaches to model the entities and their relations in large scale by knowledge graph and knowledge warehouse,and ways to discovery new entities and the relations between them in the cyberspace are discussed.